Peran Guru Kristen Sebagai Penuntun Siswa Memulihkan Gambar dan Rupa Allah Dalam Kajian Etika Kristen [The Role of Christian Teachers in Guiding the Students to Restore the Image and Likeness of God from the Perspective of Christian Ethics] - Mery Kristina Purba; Imanuel Adhitya Wulanata Chrismastianto (Diligentia: Journal of Theology and Christian Education, 2021)
Students are image and the crown of God's creation, which students have divine attributes in them. However, because of its fall into sin the God's image has broken on students. The effects of the fall are still visible today from the high number of crimes that occur in schools. The aim of writing this paper is to find out the importance of restoring God's image and likeness to the pupil’s throught teacher’s role. The research method of this paper is literature review through relevant literacy sources. The teacher guides students to develop their talents and respond their calling for always radiate the love of Christ because only Christ's redemptive work absolutely helps students to return God's images. Restoration needs to occur on the basis of Christian ethics that is in accordance with Bible values. The restoration of God's image is important for the students because they are the image and likeness of God who has fallen into sin. As a teacher who guides the students, we must show the right attitude in life and according to Christian ethics in order to guide students to restore the God' Will. Students can explore the attitude of teacher’s life who acts as guides.